2013
DOI: 10.1186/1479-5868-10-62
|View full text |Cite
|
Sign up to set email alerts
|

Examination of mid-intervention mediating effects on objectively assessed sedentary time among children in the Transform-Us! cluster-randomized controlled trial

Abstract: BackgroundThe optimal targets and strategies for effectively reducing sedentary behavior among young people are unknown. Intervention research that explores changes in mediated effects as well as in outcome behaviors is needed to help inform more effective interventions. Therefore, the purpose of this study was to examine the mid-intervention mediating effects on children’s objectively assessed classroom and total weekday sedentary time in the Transform-Us! intervention.MethodsThe results are based on 293 chil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
64
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 87 publications
(64 citation statements)
references
References 32 publications
0
64
0
Order By: Relevance
“…Furthermore, these reductions in sitting time may partly explain why students were more on task during class time as previous studies have demonstrated the importance of activity breaks in increasing students on task behavior 12 . Whilst little is known about students' perceptions of sitting for prolonged periods throughout the school day, a recent primary school physical activity intervention on sedentary time has observed a significant intervention effect on child-reported enjoyment of standing in the classroom during the school day 51 .…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, these reductions in sitting time may partly explain why students were more on task during class time as previous studies have demonstrated the importance of activity breaks in increasing students on task behavior 12 . Whilst little is known about students' perceptions of sitting for prolonged periods throughout the school day, a recent primary school physical activity intervention on sedentary time has observed a significant intervention effect on child-reported enjoyment of standing in the classroom during the school day 51 .…”
Section: Discussionmentioning
confidence: 99%
“…In children, the Transform-Us! intervention used pedagogical strategies (e.g., 2-min standing breaks from sitting and daily 30-min standing lessons) in conjunction with standing easels and observed a 13 min/day reduction in classroom sitting time among Australian 8–9 year olds after 6 months [39]. In contrast, the European intervention, UP4FUN, used curriculum-based education strategies only (without changes to pedagogy or the classroom environment) that focused on teaching children the importance of reducing sitting and increasing physical activity.…”
Section: Discussionmentioning
confidence: 99%
“…Teacher-guided pedagogical approaches encouraging students to use the desks may enhance the effectiveness of such interventions on reducing and breaking-up sitting time. Previous research has examined the impact of teacher professional development sessions with pedagogical approaches during lessons in the absence of height-adjustable desks and observed a 13 min per day reduction in classroom sitting time [38,39]. However, the combination of pedagogical approaches and height-adjustable desks has not been investigated.…”
Section: Introductionmentioning
confidence: 99%
“…years 2/3 or years 4/5 composites) were not eligible. Based on a 37% response rate (as demonstrated in a similar study conducted in the Australian school context [ 38 ]) and an average class size in Victorian schools of 23 students per class [ 39 ], we anticipate that nine students per class will consent to take part in this pilot study. For feasibility reasons, the intention is to recruit six schools (three intervention and three control) from which a sample size of 216 children is estimated (six schools × four classes (two classes per year level) [ 40 ] × nine students).…”
Section: Methodsmentioning
confidence: 99%